1971
DOI: 10.1136/bmj.4.5785.477
|View full text |Cite
|
Sign up to set email alerts
|

Results in 1,000 Cases of Therapeutic Abortion Managed by Vacuum Aspiration

Abstract: SummaryA prospective study of 1,000 cases of termination of pregnancy by vacuum aspiration is presented and the safety of the method emphasized. By setting up special clinics and an additional weekly operating session, the maximum delay from a request to appointment is 5 days, and, if operation is advised, from appointment to operation a further 7 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Premedication, given to subjects studied as inpatients, will mask many side effects of drugs. Furthermore, earlier studies of abortion blood losses have used insensitive measurement techniques (Cullen et al, 1970;Loung et al, 1971; Lauerson and Conrad, 1974 Reports have suggested that a myometrial stimulant such as ergometrine will fail to prevent the high blood losses at abortion that may be associated with modifications in anaesthetic methods (Dunn et al, 1973) and the same drug has caused clinical difficulties at operation by inducing bronchospasm (Sellers, 1979) or collapse (Valentine, 1977). Despite this, ergometrinecontaining preparations continue as the most widely used ecbolics during legal termination of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Premedication, given to subjects studied as inpatients, will mask many side effects of drugs. Furthermore, earlier studies of abortion blood losses have used insensitive measurement techniques (Cullen et al, 1970;Loung et al, 1971; Lauerson and Conrad, 1974 Reports have suggested that a myometrial stimulant such as ergometrine will fail to prevent the high blood losses at abortion that may be associated with modifications in anaesthetic methods (Dunn et al, 1973) and the same drug has caused clinical difficulties at operation by inducing bronchospasm (Sellers, 1979) or collapse (Valentine, 1977). Despite this, ergometrinecontaining preparations continue as the most widely used ecbolics during legal termination of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported as 1 out of 400 procedures by Stone et al [149] and as 6% by Loung et al [150]. This may be due to cervical trauma, uterine perforation, or uterine atony.…”
Section: Early Complicationsmentioning
confidence: 96%
“…The incidence varies from 0.4% to 2.9% [147][148][149][150] in the first trimester, and may be as much as four times this after 12 weeks gestation [148]. These present as a heavy vaginal blood loss, associated with lower abdominal pain.…”
Section: Early Complicationsmentioning
confidence: 99%
“…Where operation is to be carried out by Karman* catheter or where it is to be carried out by Bierer metal suction curette under paracervical block no premedication is given. In the remaining patients, after premedication with Omnopon 10 mg and scopolamine 0-2 mg the patient is given, in the anaesthetic room, intravenous diazepam 10 mg, pentazocine 30 mg, and methohexitone sodium 100 mg together with ergometrine 0 5 mg, a technique described previously (Loung, Buckle, and Anderson, 1971). All arrangements having been made before admission, there is no need for the patient to be seen by a doctor before being taken to the anaesthetic room.…”
Section: Admission Arrangementsmentioning
confidence: 99%
“…Vaginal Ternmination.-The technique employed for vaginal termination has been described (Buckle, Anderson, and Loung, 1970;Loung et al, 1971). It has been modified slightly in that we prefer a higher vacuum pressure of 700 mm Hg or more with the Karman suction catheter and we avoid the use of vulsellum forceps by using Allis forceps for grasping the cervix.…”
Section: Operating Sessionmentioning
confidence: 99%